Exploring Students' Learning Difficulties Using Scientific Approach in Junior High School - Rahman, Arief Aulia; Fauziana, Fauziana (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
This study was conducted at the Junior High School of West Aceh using scientific approach in the process of teaching and learning. This study aims to determine the types of difficulties and factors that cause student learning problem during the use of the scientific approach. The method in this study is the analysis of miles and Huberman, namely data reduction, data display, and conclusion with the technique of triangulation of sources, techniques, and time. The results of the study showed that the learning difficulties of students' mathematics consisted of five components: Reading Error, Comprehension Error, Transformation Error, Process Skill Error, and Encoding Error. Besides, the factors that cause learning difficulties in mathematics come from internal factors and external factors. Internal factors derived from students include student attitudes in learning mathematics, student learning motivation is still low, body health is not optimal, and students' sensory abilities are lacking. While external factors that come from outside the students, among others, the lack of teacher teaching variation, and the use of learning media that has not been maximized. Efforts should be made to reduce the difficulty of learning mathematics by the difficulties experienced and background factors among others teaches math with fun, using instructional media concrete reproduce exercises, and collaborates with parents.